Environmental performance of window-integrated systems using dye-sensitised solar module technology in Malaysia. (15th July 2019) - Mustafa, Nur Ifthitah; Ludin, Norasikin Ahmad; Mohamed, Norani Muti; Ibrahim, Mohd Adib; Teridi, Mohd Asri Mat; Sepeai, Suhaila; Zaharim, Azami; Sopian, Kamaruzzaman
Highlights: The CED of DSSC module in this study was 18.75 GJ/kWh, contributed by fabrication and panel manufacturing stage. At 5% module efficiency, the EPBT of 2.42 years was evaluated and found to be inversely proportional to conversion efficiency and solar irradiations. GHG emission rate was strongly interrelated with module lifetime, with a minimum of 70.52 gCO2-eq /kWh at 20 years of operational lifetime. Major impact to the environment was identified from electricity consumption, FTO glass substrate, inverter and silver. Abstract: Dye-sensitised solar cell (DSSC) is an emerging type of solar cells in photovoltaic (PV) technology that are desirable because of their flexibility, easy fabrication, and has benign environmental impacts. The environmental performance of DSSC can be investigated by life-cycle assessment (LCA) to further develop this technology in a sustainable manner. This study aimed to evaluate and quantify the LCA of window-integrated PV systems using DSSC module in Malaysia. Typical indicators of solar PV such as cumulative energy demand (CED), energy payback time (EPBT), and greenhouse gas (GHG) emission rate from cradle-to-gate were assessed with SimaPro. Several environmental impacts were also observed through the Recipe Midpoint (H) method. Results showed that the CED produced throughout the DSSC life cycle was 18.75 GJ/kWh, EPBT of 2.42 years and GHG emission rate of 70.52 gCO2-eq /kWh. Moreover, extensive electricity consumption during module fabrication and panel manufacturing processes using Malaysia's energy mix, as well as the use of glass substrates, silver and inverter, were some of the factors that have been identified in this research that affected CED, EPBT, GHG emission rate and a number of environmental impacts including metal depletion, freshwater ecotoxicity, marine ecotoxicity, freshwater eutrophication, human toxicity and fossil depletion.